Principles and methods of securing industrial ecological safety - Белов, П. Г.; Запорожченко, Ю. Ф. (Proceedings of National Aviation University (archive), 1999)
Proposed is classification of risks, determined is regularity and factors of technogenic accidents, proposed is energoentropic concept of technogenic risks, considered are the principles and methods of securing industrial and ecologic safety